Uterus Model as Learning Media to Improve Skill in Handling Post Partum Haemorrhage - Dwi Purwanti; Sriami Sriami; Titi Maharrani (Humanistic Network for Science and Technology (HNST), 2018)
One of midwifery student’s competences is can handle postpartum haemorrhage. Thus, it is needed learning of ideal laboratory practice through learning media of uterus model, which it resembles the real uterus organ. Meanwhile, the available learning media of uterus model is still less sufficient, hence, it needs to be conducted a research regarding learning media of uterus model that resembles its original uterus organ so that it will be easier to be understood by the students. Moreover, this research aimed at conducting evaluation of the available uterus model, arranging learning development through uterus model media, and conducting field experiment I. Design of this research was experimental research, which the research was conducted through experiment of making learning media in form of uterus model. Afterwards, it was analyzed by utilizing Test. The result showed evaluation against available uterus model, which most of them were not appropriate with uterus structure (73.16%). Development of learning media resulted uterus model product, which afterwards, it was conducted field experiment I and it showed that there was a significant difference of understanding between available uterus model and developed uterus model (p-value = 0.000). Therefore, it was suggested to conduct further research in stage II that involved test against uterus model function of development result and to recommend the development result to users and professionals. Keywords: Learning media, Uterus model, postpartum haemorraghe